Generation of in vivo activating factors in the ischemic intestine by pancreatic enzymes - Mitsuoka, Hiroshi (The National Academy of Sciences, 2000)
One of the early events in physiological shock is the generation of activators for leukocytes, endothelial cells, and other cells in the cardiovascular system. The mechanism by which these activators are produced has remained unresolved. We examine here the hypothesis that pancreatic digestive enzymes in the ischemic intestine may be involved in the generation of activators during intestinal ischemia. The lumen of the small intestine of rats was continuously perfused with saline containing a broadly acting pancreatic enzyme inhibitor (6-amidino-2-naphthyl p-guanidinobenzoate dimethanesulfate, 0.37 mM) before and during ischemia of the small intestine by splanchnic artery occlusion. This procedure inhibited activation of circulating leukocytes during occlusion and reperfusion. It also prevented the appearance of activators in portal venous and systemic artery plasma and attenuated initiating symptoms of multiple organ injury in shock. Intestinal tissue produces only low levels of activators in the absence of pancreatic enzymes, whereas in the presence of enzymes, activators are produced in a concentration- and time-dependent fashion. The results indicate that pancreatic digestive enzymes in the ischemic intestine serve as an important source for cell activation and inflammation, as well as multiple organ failure.